Analysis technology and application of natural fractures based on microseismic monitoring results. Issue 4 (April 2020) - Li, Hao; Fan, Li; Qin, Li; Tang, Yong; Huang, Yaqiu
Abstract: In general, the matrix permeability of shale reservoirs is small, and a developed natural fracture network is required to obtain a good mining effect. Therefore, analyzing and understanding the development of natural fractures in the reservoir plays an important role in increasing the production capacity of shale gas. Microseismic monitoring is the key technology of fracture imaging during hydraulic fracturing. Based on the results of ground microseismic monitoring, this paper analyzed both the waveform and energy of microseismic event, as well as the spatial distribution law, and also combined it with the surface seismic attribution data, formed a natural fracture analysis technology based on the results of microseismic monitoring, which played an important supporting role in real-time optimization and guidance of hydraulic sand fracturing.